ТHE METAPHORICAL ASPECT OF THE STUDY OF CREATIVITY A. AKHMATOVA (Scientific journal of the Fergana State University, 2023)
Russian poetess, translator A.Akhmatova is one of the most significant figures of Russian literature of 20 th century.This article is devoted to the study of the role of metaphor in the work of Akhmatova.